Effects of organic nutrient management on aromatic rice (Oryza sativa)-linseed (Linum usitatissimum) sequence - SARMAH, ANJAN K; CHOUDHARY, J K; DEKA, J; PATHAK, K; DAS, K N; KALITA, P (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2019 and 2020 at the Instructional-cum Research (ICR) Farm, Assam Agricultural University, Jorhat, Assam to study the impact of different combinations of organic nutrient sources on aromatic rice (Oryza sativa L.) (rainy-kharif) and their residual effect on linseed (Linum usitatissimum L.) (winter- rabi) crop for developing a double cropping sequence for rice growers of Assam with organic management. The experiment comprised three aromatic rice cultivars, viz. Kola joha, Keteki joha and Chakhao poireiton and five combinations of organic nutrient sources. Out of the organic nutrient sources, application of N @30 kg/ha through vermicompost along with pre-season green manuring of Sesbania bispinosa and root dip treatment of rice seedlings with Azospirillium and phosphorus solubilising bacteria @3.5 kg/ha each (N3) resulted the highest number of panicles/ m2 (216.72 in 2019 and 223.96 in 2020), highest yield of rice (30.26 q/ha in 2019, 32.58 q/ha in 2020 grain yield and 65.99 q/ha in 2019, 68.98 q/ha in 2020 straw yield). The highest seed yield (394.52 kg/ha in 2019, 416.97 kg/ha in 2020) and stover yield (890.09 kg/ha in 2019, 896.63 kg/ha in 2020) of succeeding relay sown linseed were recorded with the N3 treatment. The highest available N (250.10 kg/ha), P2O5 (20.40 kg/ha) and K2O (140.06 kg/ha), organic C (0.65%), soil organic carbon (SOC) stock (13.29 t/ha), soil microbial biomass carbon (SMBC) (183.43 µg/g of soil) in soil were recorded with the N3 treatment after harvest of linseed in 2020. The study affirmed the suitability of rice-linseed cropping sequence for efficient utilization and conservation of resources.